Capture and estimate the speed of the object for remote monitoring / Nor Sajidah Ab Ghani - Ab Ghani, Nor Sajidah (2016)
The webcam is normally used for recording and capturing the image to sending a live video over conference calls or uploading the image to the social network. However, the use of webcams is seldom used for recognition of an object. In this work, the webcam is considered as Close Circuit Television (CCTV). Besides that, this work can applied in the traffic police to monitor the speed of vehicles in normal roads. The webcam is employed to analyse the type of object and detected the speed of an object. The USB webcam and Matlab & Simulink are utilized to design a system for of the vehicle movement monitoring system. A USB webcam is employed to record the vehicles as well as object movement respectively. The software used to record the movement and tracking the object is computer vision and image processing. The software is tested when there is movement as the camera captured the image. The video processing in computer vision is used to record the video when has motion in video. After that, the video is analysed in the image processing using optical follow technique. For any changes pixel in the video are recorded and it was analysed using the optical flow image processing. The optical flow used Kanade Lucas Algorithm method to track the vehicle movement in the video. After tracking the vehicle, the centroid is used to determine the location of a vehicle at a given frame. Then, the Euclidean method is used to calculate the distance between the pixels to estimate the speed. The speed is only changed when the pixels are changed